Diffusion Abnormality in Temporal Lobe Epilepsy Patients With Sleep Disorders: A Diffusion Kurtosis Imaging Study - Guo, Min; Shen, Boxing; Li, Jinhong; Huang, Xiaoqi; Hu, Jie; Wei, Xiaocheng; Wang, Shaoyu; Yuan, Ruohan; He, Chengcheng; Li, Yanjing (Frontiers in Psychiatry, 2022)
Background: Patients with temporal lobe epilepsy (TLE) frequently complain of poor sleep quality, which is a condition that clinicians are typically neglecting. In this study, Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), and Athens Insomnia Scale (AIS) were used to assess the sleep status of patients with temporal lobe epilepsy (TLE) and simultaneously diffusion kurtosis imaging (DKI) was applied to examine the white matter microstructure abnormalities in patients with TLE and sleep disorders. Methods: TLE patients who have been diagnosed in the cardio-cerebrovascular ward of the Yanan University Affiliated Hospital from October 2020 to August 2021 were recruited. Finally, 51 patients and 30 healthy controls were enrolled in our study, with all subjects completing the sleep evaluation questionnaire and undergoing a DKI examination. An independent sample t-test, analysis of variance (ANOVA), and Mann-Whitney U test were used to compare groups. Results: Thirty patients (55.89%) complained of long-term sleep difficulties. The differences among the evaluation of AIS, ESS, and PSQI are statistically significant (p=0.00, p=0.00, p=0.03). The scores of L/R-TLE in AIS, ESS, as well as PSQI in L-TLE with sleep disorders, are statistically higher than the control group (p=0.00, p=0.00, p=0.00, p=0.00, p=0.02). L-TLE with sleep disorders showed decreased MK on affected sides (p=0.01). However, statistically significant differences in MD and FA have not been observed (p=0.34, p=0.06); FA in patients with sleep disorder is less than those without. R-TLE with sleep disorders showed significantly decreased MK and increased MD on affected sides (p=0.00, p=0.00), but FA's statistically significant difference has not been observed (p=0.20). Conclusions: TLE patients frequently experience insomnia, poor nighttime sleep quality, and excessive daytime drowsiness. TLE patients with sleep disorders have different DKI parameters than individuals who do not have sleep issues. During this process, the kurtosis parameter (MK) was discovered to be more sensitive than the tensor parameters (MD, FA) in detecting the patient's aberrant white matter diffusion. DKI may be a better choice for in vivo investigation of abnormal craniocerebral water diffusion.